A hybrid variable neighborhood search for the Orienteering Problem with mandatory visits and exclusionary constraints. (February 2017) - Palomo-Martínez, Pamela J.; Angélica Salazar-Aguilar, M.; Laporte, Gilbert; Langevin, André
Abstract: This paper addresses a variant of the Orienteering Problem in which some constraints related to mandatory visits and incompatibilities among nodes are taken into account. A hybrid algorithm based on a reactive GRASP and a general VNS is proposed. Computational experiments over a large set of instances show the efficiency of the algorithm. Additionally, we also validate the performance of this algorithm on some instances taken from the literature of the traditional Orienteering Problem. Abstract : Highlights: This paper addresses the Orienteering Problem (OP) with mandatory visits and exclusionary constraints. An efficient procedure based on a reactive GRASP and a general VNS is proposed. Extensive computational results on artificial instances are analyzed. Additionally, the performance of the proposed procedure is validated on a set of instances taken from the literature of the traditional OP.